Aplicaciones de minicomputadoras - Portilla R., Marcial; Guzmán A., Adolfo; Segovia, Raymundo (My University, 1976)
Where computers fit. Scientists and engineers describe, measure, interpret, and predict the outside world in terms of idealized mathematical models, wich relate numerical quantities and truth values through various mathematical operations.
Keywords: arquitectura; sistema operativo de tiempo real; interrupciones; software; memory and computation